Akuntabilitas Pengelolaan Keuangan Di Masjid Syuhada Masamba Berdasarkan PSAK 45 - Nasaruddin Nasaruddin; Muh. Abdi Imam (ITB AAS INDONESIA, 2023)
The purpose of this research is to determine how the form of the Masamba Syuhada Mosque's financial statements and the suitability of the financial statements prepared at the Masamba Syuhada Mosque with PSAK 45. The research methodology used in this study is interpretive qualitative with a case study approach. This study was conducted in the city of Masamba, Kab. North Luwu. The analysis technique utilized is logic analytic, which involves modifying numerous observations and interviews with the theory used, which is accounting and religion, good governance, and jurisdictional clashes. Only record the amount of entering and exiting cash, and financial statements are not prepared in line with PSAK 45 for non-profit businesses. Keywords : Accounting and theology, good governance, Clash Of Jurisdictional, Mosque Accounting, PSAK 45